Stable Robust Adaptive Control of Induction Motors with Unknown Parameters - Jasim, Ibrahim (Iraqi Journal for Electrical and Electronic Engineering, 2010)
This paper presents a new strategy for controlling induction motors with unknown parameters. Using a simple linearized model of induction motors, we design robust adaptive controllers and unknown parameters update laws. The control design and parameters estimators are proved to have global stable performance against sudden load variations. All closed loop signals are guaranteed to be bounded. Simulations are performed to show the efficacy of the suggested scheme.